Benchmarking of Siemens Linac in Electron Modes: 8-14 MeV Electron Beams - Dowlatabadi H. (Journal of Biomedical Physics and Engineering, 2018)
Introduction: Radiation therapy using electron beams is a promising method due to its physical dose distribution. Monte Carlo (MC) code is the best and most accurate technique for forespeaking the distribution of dose in radiation treatment of patients.